Prevalence of Plasmodium Falciparum and Plasmodium Vivax in Choti Zareen, Dera Ghazi Khan, Pakistan - Tabish, Saba; Zaheer, Naireen; Sahar, Akash; Abbas, Mustansar; Saghir, Rubab; Batool, Fareeha; Iftikhar, Muhammad Madni; Kamal, Muhammad; Qadeer, Iqra; Khan, Gul Zahra (Indus Journal of Bioscience Research, 2025)
Plasmodium is and endoparasite of human, which belongs to class apicomplexan of Protista. There are many species of this parasite, but here we study about two, which are majorly occurring in Pakistan. Our research area for study was Choti Zareen, D.G Khan, Pakistan. We study the different groups of peoples on the bases of Sex/ Gender, Age, Education, and Socio-economic status. The ratio of malarial disease was higher in females than males, in early age children’s and aged peoples than juvenile, in uneducated than educated peoples and in socio-economic peoples and poverty’s ones. In this study, 200 human blood samples were collected from Choti Zareen, Dera Ghazi Khan to determine the prevalence of Plasmodium falciparum and Plasmodium vivax. The overall malaria prevalence was found to be 25.5%, with P. vivax (90.1%) being more prevalent than P. falciparum (52.9%). Age-wise distribution revealed the highest prevalence (37.5%) in the 51–60 years group and the lowest (16.6%) in the 61–70 years group. Males showed a higher infection rate (32.2%) compared to females (20%). A negative correlation was observed between educational level and prevalence: uneducated individuals had a higher rate (28.5%) than those with secondary or higher education (18.42%). Socioeconomic status also played a role, with the highest prevalence in the lower class (32.1%) and the lowest in the upper class (17.2%). These findings suggest that age, sex, education, and socioeconomic factors significantly influence malaria transmission in the region, highlighting the need for targeted awareness and control measures.